Antiepileptic drug use improves overall survival in breast cancer patients with brain metastases in the setting of whole brain radiotherapy. Issue 2 (November 2015) - Reddy, Jay P.; Dawood, Shaheenah; Mitchell, Melissa; Debeb, Bisrat G.; Bloom, Elizabeth; Gonzalez-Angulo, Ana M.; Sulman, Erik P.; Buchholz, Thomas A.; Woodward, Wendy A.
Abstract: Background and purpose: There is mounting evidence that histone deacetylase (HDAC) inhibitors, e.g. valproic acid (VPA), synergize with radiation to improve outcomes in several cancers. This study was conducted to ascertain whether VPA affected outcomes in breast cancer patients with brain metastases treated with whole brain radiotherapy (WBRT). Materials and methods: Records from 253 breast cancer patients with brain metastases treated with WBRT were reviewed. Data regarding use of all antiepileptic drugs (AEDs) were extracted. Kaplan–Meier survival times were calculated using the date of brain involvement as time zero. Cox proportional hazard models were used to determine the association between patient and tumor characteristics and overall survival (OS). Results: Median OS for the entire patient cohort was 6 months. Patients receiving VPA ( n  = 20) had a median OS of 11 months versus 5 months for those not receiving VPA ( p  = 0.028). Median OS was 9 months for patients taking any AED ( n  = 101) versus 4 months for those not taking AEDs ( p  = 0.0003). On multivariate analysis both VPA and AED use were associated with improved OS (HR 0.61, p  = 0.0419; HR 0.59, p  = 0.0002, respectively). Conclusions: This study suggests the use of AEDs, including VPA, is associated with improved OS in breast cancer patients with brain metastases following WBRT.